Using multimedia and the internet as a bulletin board for SEE 3523 the electromagnetic theory - 266001 Mohamed Abd Manap (Sekudai : UTM, 1996)
Projek paper (Bachelor of Electrical Engineering) - Universiti Teknologi Malaysia, 1996